Energy-Efficient Communication Networks and Systems - Lorincz, Josip (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint "Energy-efficient communication networks and systems" gives insights into the range of problems in the field of obtaining more energy-efficient communication networks and systems. The reprint contains the outcomes of the "Special Issue on energy-efficient communication networks and systems" organized for the Sensors journal published by the Multidisciplinary Digital Publishing Institute (MDPI). The 12 high-quality papers published in the frame of the Sensors journal Special Issue have been collected and reproduced in this book, demonstrating significant achievements in the field to which this reprint is dedicated.Published papers consolidated in this reprint are self-contained peer-reviewed scientific works. Among published papers, one paper is editorial, one paper is a review type of paper, and the remaining ten articles are research articles. The papers are authored by 40 authors coming from academia and industry. The published articles target the improvement of energy efficiency in the fields of fiber-wireless, vehicle-to-vehicle/infrastructure, sensors, satellites, 5G, virtual elements, and cognitive radio networks. The contributions of published papers provide valuable insights into the latest research and technologies for improving the energy efficiency of communication networks and systems.This reprint can serve the readers as a source of information when needed in their industrial, teaching and/or research and development activities since it presents the recent advances in different fields related to improving the energy efficiency of communication networks and systems.